Maintenance Time and the Industry Development of Patents Empirical Research With Evidence from China. - Qiao, Yongzhong (Springer Verlag, 2017)
This book addresses key issues concerning the maintenance time and development of patents granted by China, as well as the patent maintenance time granted by the United States, Germany, France, Japan and South Korea. Such issues include the capability of technological innovation based on the patent maintenance time; the patent maintenance times in different technological fields granted by China, the United States, Germany, France, Japan and South Korea; the distribution of patented technologies in the energy-saving industry, the patent protection of Traditional Chinese Medicine, the impact on the R & D industry in China, and so on. This book presents theoretical perspectives on technological innovations promoted by the patent system and proposes a number of recommendations to reform the annual fee system of maintaining patents and optimize the patent maintenance time. The materials presented here comprise original and innovative contributions, with a special focus on empirical data and scholarly analysis.
Keywords: Patents.; elektronické knihy; electronic books